2020
DOI: 10.1214/20-ejs1710
|View full text |Cite
|
Sign up to set email alerts
|

Univariate mean change point detection: Penalization, CUSUM and optimality

Abstract: The problem of univariate mean change point detection and localization based on a sequence of n independent observations with piecewise constant means has been intensively studied for more than half century, and serves as a blueprint for change point problems in more complex settings. We provide a complete characterization of this classical problem in a general framework in which the upper bound σ 2 on the noise variance, the minimal spacing ∆ between two consecutive change points and the minimal magnitude κ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 45 publications
3
79
0
Order By: Relevance
“…Remark In a recent article Wang et al (2019) investigated optimality properties for mean change point detection and localization in model () with a piecewise constant function and independent identically distributed sub‐Gaussian errors. In particular they derived necessary and sufficient conditions under which consistent localization of the change points is possible and derived the minimax optimal rate.…”
Section: Asymptotic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark In a recent article Wang et al (2019) investigated optimality properties for mean change point detection and localization in model () with a piecewise constant function and independent identically distributed sub‐Gaussian errors. In particular they derived necessary and sufficient conditions under which consistent localization of the change points is possible and derived the minimax optimal rate.…”
Section: Asymptotic Propertiesmentioning
confidence: 99%
“…In particular they derived necessary and sufficient conditions under which consistent localization of the change points is possible and derived the minimax optimal rate. Wang et al (2019) also demonstrated that localization based on an ℓ 0 ‐penalized least squares approach or wild binary segmentation achieves a rate that is minimax optimal up to a logarithmic factor. It follows from theorem 7 in Frick et al (2014) that in the case of independent identically normal distributed errors SMUCE also attains the minimax optimal rate up to a logarithmic factor.…”
Section: Asymptotic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a frequent jump regime i is small (related to outlier detection) and necessarily corresponding jumps f ′ i need to be large to be detectable. In both situations, an adaptation of Lemma 1 of Wang et al (2018) shows that no consistent estimator of the locations of change point exists when −2 min 1≤i≤N ( i (f � i ) 2 ) < log(T). While WBS2.SDLL is shown to perform well in both regimes numerically, the paper does not provide a theoretical underpinning of this good behaviour, in the sense that only a linear-time change point setting with T ∶= min i i being of the same order as the sample size T is considered: Such an assumption is not necessary for consistent change point detection and, moreover, it excludes models such as extreme.teeth (ET) and extreme.extreme.teeth (EET), which are reasonably considered as belonging to the frequent jump regime with T ≤ 5 .…”
Section: Theoretical Propertiesmentioning
confidence: 99%
“…In addition, the best currently available results for the localisation rate attained by WBS as well as the requirement on the magnitude of changes for their detection, are sub-optimal when T ∕T → 0 (see Appendix A of Cho and Kirch 2019). Baranowski et al (2019) and Wang et al (2018) suggest modifications of WBS that alleviate the sub-optimality at the cost of introducing additional tuning parameters such as a threshold or an upper bound on the length of random intervals. However, even in these papers, the assumptions are formulated in terms of…”
Section: Theoretical Propertiesmentioning
confidence: 99%